2013
DOI: 10.3892/mmr.2013.1276
|View full text |Cite
|
Sign up to set email alerts
|

Palmitate induces H9c2 cell apoptosis by increasing reactive oxygen species generation and activation of the ERK1/2 signaling pathway

Abstract: Cardiac myocytes undergo apoptosis under conditions of high free fatty acid concentrations, including palmitate, which is implicated in lipotoxic cardiomyopathy. However, the underlying mechanisms remain unknown. The aim of the present study was to understand the role of reactive oxygen species (ROS) production and the extracellular signal‑regulated kinase 1/2 (ERK1/2) signaling pathway in palmitate‑induced apoptosis in H9c2 cells. H9c2 cells were exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 43 publications
(53 reference statements)
6
22
0
Order By: Relevance
“…However, the role of ROS in stimulating lipoapoptosis appears to be cell-type dependent as palmitate-treated neonatal cardiomyocytes undergo apoptosis independently of the oxidative stress [33]. In the current study, ROS production was identified at increased levels following palmitate-induced apoptosis in HepG2 cells, consistent with previous studies [21,32,34]. We also found that ascorbic acid co-treatment simultaneously normalized palmitate-induced ROS …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, the role of ROS in stimulating lipoapoptosis appears to be cell-type dependent as palmitate-treated neonatal cardiomyocytes undergo apoptosis independently of the oxidative stress [33]. In the current study, ROS production was identified at increased levels following palmitate-induced apoptosis in HepG2 cells, consistent with previous studies [21,32,34]. We also found that ascorbic acid co-treatment simultaneously normalized palmitate-induced ROS …”
Section: Discussionsupporting
confidence: 93%
“…We also observed an increased FOXO-1 phosphorylation in parallel with Another mechanism linking SHIP2 to apoptosis is oxidative stress. A growing body of evidence suggests that the oxidative stress due to excessive production of ROS is the main contributor to the pathophysiology of diabetic complications [21,30]. Increasing ROS production has been demonstrated to account for apoptosis in response to palmitate in numerous cell lines [31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In neonatal rat ventricular myocytes, NAC and MAPK inhibitors failed to rescue PA-induced apoptosis. However, another study using H9c2 cells as the research object supports our conclusion, which showed that ERK inhibitor reduced PA-induced 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 apoptosis through partial suppression of intracellular ROS generation, suggesting important roles of MAPKs and ROS in H9c2 cells [4]. Thus, we speculate that the effects of PA may be cell type specific and the exact roles of ROS and MAPKs need to be verified in vivo.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have proposed that PA promotes ROS production in different cardiac cell types [4e8]. Although Wei et al reported that U0126, an inhibitor of extracellular signal-regulated kinase (ERK), reduced PA-induced apoptosis through partial suppression of intracellular ROS generation, there was no direct evidence to prove the involvement of ROS [4]. A recent study demonstrated that autophagy was induced by PA as an adaptive response to ER stress since it was sensitive to ER stress inhibition in H9c2 cells [9], however, whether ROS plays a role in PA-induced autophagy and apoptosis remains unknown.…”
Section: Introductionmentioning
confidence: 99%